(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article presents alternative approaches to enhancing listening and reading skills in technical college students. Listening and reading are critical receptive skills necessary for understanding academic content, technical manuals, and professional communication. The article explores factors affecting students’ performance, such as cognitive load, limited authentic input, and motivational challenges. Practical teaching strategies discussed include task-based learning, multimedia integration, collaborative learning, and reflective exercises. The findings indicate that diverse, learner-centered strategies promote comprehension, vocabulary acquisition, and critical thinking, preparing students for both academic and professional success